2019
DOI: 10.1007/s12603-019-1273-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical Frailty: ICFSR International Clinical Practice Guidelines for Identification and Management

Abstract: Objective: The task force of the International Conference of Frailty and Sarcopenia Research (ICFSR) developed these clinical practice guidelines to overview the current evidence-base and to provide recommendations for the identification and management of frailty in older adults. Methods: These recommendations were formed using the GRADE approach, which ranked the strength and certainty (quality) of the supporting evidence behind each recommendation. Where the evidence-base was limited or of low quality, Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
608
4
55

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 618 publications
(674 citation statements)
references
References 173 publications
(234 reference statements)
7
608
4
55
Order By: Relevance
“…A.M. ABBATECOLA 1,2 , R. ANTONELLI-INCALZI 3,4 in the ratio of angiotensin receptor-1 (AT-1) to angiotensin receptor-2 (AT-2) in pulmonary regions with marked fibrosis (12). AT-2s have been shown to hold anti-fibrotic properties, while AT-1s seem to hold a role in COPD-lung induced fibrosis (12).…”
Section: Covid-19 Spiraling Of Frailty In Older Italian Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A.M. ABBATECOLA 1,2 , R. ANTONELLI-INCALZI 3,4 in the ratio of angiotensin receptor-1 (AT-1) to angiotensin receptor-2 (AT-2) in pulmonary regions with marked fibrosis (12). AT-2s have been shown to hold anti-fibrotic properties, while AT-1s seem to hold a role in COPD-lung induced fibrosis (12).…”
Section: Covid-19 Spiraling Of Frailty In Older Italian Patientsmentioning
confidence: 99%
“…Frailty should be considered a constantly evolving syndrome and only reversible if appropriate intervention is quickly recognized and applied. Indeed, there is substantial literature underlining the importance of geriatric medicine toward frailty prevention and clinical criteria to rapidly identify those with frailty or pre-frailty (3)(4)(5). If any negative health conditions break the equilibrium, the irreversible downward spiraling of frailty will begin.…”
mentioning
confidence: 99%
“…Persons with comorbidity are at an increased risk. It is suggested that the FRAIL screen is used to detect persons at increased risk (6,7,8). Persons with hypertension and diabetes mellitus are at increased risk possibly due to alterations in the angiotensin converting enzyme 2 (ACE 2) receptor produced by ACE 1 inhibitors.…”
mentioning
confidence: 99%
“…An increased amount of physical activity, exercise, adequate protein intake and appropriate medication are thought to be the first-line therapies in the management of frailty [105][106][107] and comprehensive and individualized prescribed treatment interventions can improve or slow down the deterioration 108 .…”
Section: Physical Activity and Exercise In The Treatment Of Frailtymentioning
confidence: 99%
“…It is recommended that frailty screening to identify frailty and facilitate risk stratification should be performed with instruments that capture multiple domains of the frailty syndrome 40 . Since frailty is strongly related to progressive disability 32 , additional assessments focusing on components of physical fitness should also be made of patients identified as frail 107 . Greater attention to the physical domains, at an early stage during the hospital stay, would probably facilitate the tailoring of interventions adapted to suit each patient.…”
Section: Benefits Of Assessment Of Physical Fitness In Medical In-hosmentioning
confidence: 99%